Additional earnings as a source of filling peasant budgets in the NEP Era (1921–1928) - Священко, Зінаїда; Terpan, Iryna (Ukrainian Peasant, 2024)
Abstract. Purpose. The goal is to highlight, on the basis of a comprehensive analysis of historical material, the peculiarities of the formation of the budget of peasant farms of Ukraine in the conditions of the NEP, and to determine the specific weight of additional earnings as a source of monetary income for peasant farms of various economic categories. Scientific novelty. The scientific novelty is that for the first time in modern domestic historiography, additional earnings are considered as a source of filling peasant budgets during the NEP period and their correlation with other actual sources of income of peasant households. Quantitative and qualitative indicators of the participation of peasants in trades, types of earnings outside of agriculture, the priority of trades as a source of monetary income for peasant farms of the Ukrainian SSR of various economic categories are analyzed. Conclusions. In the income part of peasant budgets, auxiliary industries, trades and seasonal side jobs played an important role. A significant stratum of the rural population consisted of peasants engaged in artisanal trades – potters, blacksmiths, carpet makers, carpenters, millers, weavers, tailors, shoemakers, stelmachs. They produced up to 70% of the products of the small-scale industry of Ukraine. Despite the ban, such a craft as moonshine became popular in the village. During the NEP period, in order to balance the budget of their farms, peasants were forced to engage in various household and recreational activities, working at various jobs outside their farms. The number of farms (mainly those with little land) that resorted to this method of supplementing peasant budgets grew steadily and reached almost 50% by the end of the 1920s. Simultaneously with the increase in the number of people working outside their farms, the share of income of peasant farms from earnings not related to work on their farms also increased. In 1926, wage earnings in all branches of production were the main source of livelihood for 9.6% of all peasant households, and for 28.1% they served as the main source of cash income.